Effect of conservation agriculture on soil hydro-physical properties under diversified maize (Zea mays)-based cropping systems - Yadav, Brijesh; Krishnan, Prameela; Parihar, C M; Yadav, Suresh (The Indian Journal of Agricultural Sciences, 2020)
Rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system of the Indo-Gangetic Plains is under threat due to multiple challenges of degrading soil structure, depleting soil organic carbon, declining water level and increasing multi-nutrient deficiencies making farming uneconomical and unsustainable. Conservation agriculture (CA) based tillage practices along with optimization of cropping systems have shown to produce more with less inputs. Therefore, an experiment was conducted to evaluate the impact of tillage practices, viz. zero tillage with residue retention (ZT + R) and conventional tillage with residue incorporation (CT + R), under diversified maize based cropping system (maize-wheat-mungbean and maize-mustard-mungbean) on soil hydro-physical properties at IARI, New Delhi. Compared to CT+R, bulk density (BD) showed significant (P < 0.05) decline (3.4-7.7% and 1.2 -2.4 %) under ZT+R at 0–30 and 30-60 cm soil depths but the impact of cropping system was non-significant. The saturated hydraulic conductivity(Ksat) was significantly (P < 0.05) increased by 12.1, 13.9, 20.0 and 17.6% under ZT+R for 0–15, 15–30, 30-45 and 45-60 cm soil depths, respectively as compared to CT+R. Initial and final infiltration rate and cumulative infiltration were significantly higher in ZT+R than CT+R. Overall, our results suggest that adoption of zero tillage with residue retention under maize-wheat-mungbean (MWMb) systems can improve the soil hydro-physical properties.